2013
DOI: 10.1002/lary.23800
|View full text |Cite
|
Sign up to set email alerts
|

Snoring intensity after a first session of soft palate radiofrequency

Abstract: Snoring sound intensity after the first RF session helps predict the final outcome of RF-assisted stiffening of the soft palate for simple snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The efficacy of RF surgery has been demonstrated in numerous prospective clinical trials. The short‐term efficacy of this treatment includes reduction in snoring, excessive daytime sleepiness, and OSA severity 1724,1728–1735 . An SR by Bäck et al.…”
Section: Surgical Treatment For Osamentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of RF surgery has been demonstrated in numerous prospective clinical trials. The short‐term efficacy of this treatment includes reduction in snoring, excessive daytime sleepiness, and OSA severity 1724,1728–1735 . An SR by Bäck et al.…”
Section: Surgical Treatment For Osamentioning
confidence: 99%
“…The short-term efficacy of this treatment includes reduction in snoring, excessive daytime sleepiness, and OSA severity. 1724,[1728][1729][1730][1731][1732][1733][1734][1735] An SR by Bäck et al demonstrated that RF of the soft palate could reduce symptoms of snoring, at least in the short term. 1736 On the contrary, the latest RCT conducted by Holmlund's group reported no significant clinical benefit on daytime sleepiness, snoring, or apnea severity one year after RF palatoplasty.…”
Section: Ixd4d Transpalatal Advancement Pharyngoplastymentioning
confidence: 99%
“…After Fujita et al 8 introduced uvulopalatoplasty in 1981, various techniques were added for the management of snoring, including cautery-assisted palatal stiffening operation, injection snoreplasty radiofrequency ablation, pillar palatal implants, and laser-assisted uvulopalatoplasty (LAUP). 5,[9][10][11] Surgical treatments have some disadvantages, such as pain, speech problems, hospitalization, and extra care after operation. Nonsurgical procedures such as dental appliances that open upper airways, oral tablets, nasal dilators, nasal lubricants, and Continuous Positive Airway Pressure (CPAP) treatment are also available 12,13 and they can be easily performed.…”
Section: Introductionmentioning
confidence: 99%
“…The short-term efficacy of this treatment includes reduction in snoring, excessive daytime sleepiness, and OSA severity. 1723,[1727][1728][1729][1730][1731][1732][1733][1734] A systematic review by Bäck demonstrated that RF of the soft palate could reduce symptoms of snoring, at least in the short term. 1735 On the contrary, the latest randomized controlled trial conducted by Holmlund's group reported no significant clinical benefit on daytime sleepiness, snoring, or apnea severity one year after RF palatoplasty.…”
Section: Ixd4e Radiofrequency Palatoplastymentioning
confidence: 99%